2022
DOI: 10.3390/ijms23073717
|View full text |Cite
|
Sign up to set email alerts
|

ENPP2 Promoter Methylation Correlates with Decreased Gene Expression in Breast Cancer: Implementation as a Liquid Biopsy Biomarker

Abstract: Autotaxin (ATX), encoded by the ctonucleotide pyrophosphatase/phosphodiesterase 2 (ENPP2) gene, is a key enzyme in lysophosphatidic acid (LPA) synthesis. We have recently described ENPP2 methylation profiles in health and multiple malignancies and demonstrated correlation to its aberrant expression. Here we focus on breast cancer (BrCa), analyzing in silico publicly available BrCa methylome datasets, to identify differentially methylated CpGs (DMCs) and correlate them with expression. Numerous DMCs were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 38 publications
0
17
1
Order By: Relevance
“…Furthermore, in an analysis of circulating cell free DNA (ccfDNA), ENPP2 was also found hypermethylated but failed to find any significant difference between methylation levels of healthy and BC patients [ 63 ]. In contrast to that, in our recent work, methylation of ENPP2 1st exon in ccfDNA was found significant hypermethylated in BC patients as compared to healthy ccfDNA and it was also correlated with the cancer load [ 13 ], suggesting a role of ENPP2 methylation as a BC prognostic biomarker. These controversial results could be methodologically explained due to the different regions of ENPP2 gene that were examined in the patient samples.…”
Section: Enpp2 Methylation and Cancercontrasting
confidence: 88%
See 3 more Smart Citations
“…Furthermore, in an analysis of circulating cell free DNA (ccfDNA), ENPP2 was also found hypermethylated but failed to find any significant difference between methylation levels of healthy and BC patients [ 63 ]. In contrast to that, in our recent work, methylation of ENPP2 1st exon in ccfDNA was found significant hypermethylated in BC patients as compared to healthy ccfDNA and it was also correlated with the cancer load [ 13 ], suggesting a role of ENPP2 methylation as a BC prognostic biomarker. These controversial results could be methodologically explained due to the different regions of ENPP2 gene that were examined in the patient samples.…”
Section: Enpp2 Methylation and Cancercontrasting
confidence: 88%
“…In our recent in silico analysis of ENPP2 methylation in BC tissues, it was found that the promoter CGs were hypermethylated in comparison to normal tissues and mRNA expression was downregulated and inversely correlated with the methylation. Hypermethylation of ENPP2 was also associated with the progression of BC [ 13 ]. Together, these findings suggest that ENPP2 is highly methylated in BC, correlated with aggressiveness and low expression levels.…”
Section: Enpp2 Methylation and Cancermentioning
confidence: 99%
See 2 more Smart Citations
“…It is noteworthy that promoter methylation plays an important regulatory role in gene expression [ 30 32 ]. Although previous studies have reported that MEF2C-AS1 was downregulated in DGC [ 27 ] and CC [ 28 ] lesion tissues, and BC [ 29 ] cells, the current study is the first that systematically described the MEF2C-AS1 methylation status and its influence on expression.…”
Section: Discussionmentioning
confidence: 99%